Timing of Wnt Inhibition Modulates Directed Differentiation of Medial Ganglionic Eminence Progenitors from Human Pluripotent Stem Cells - Ivanna Ihnatovych; Alexandra Lew; Evelyn Lazar; Anna Sheng; Timot Kellermayer; Kinga Szigeti (Stem Cells International)
In vitro differentiation of human pluripotent stem cell into relevant cell types is a desirable model system that has the human biological context, is a renewable source, and is scalable. GABA interneurons and basal forebrain cholinergic neurons, derivates of the medial ganglionic eminence (MGE), are implicated in diverse neuropsychiatric diseases. Various protocols have been proposed to generate MGE progenitors: the embryoid body- (EB-) based rosette-derived (RD), the adherent (AdD), and the nonadherent (NAdD) approaches. While Wnt inhibition is frequently incorporated into the strategy, the timing varies between protocols and there is a lack of standardized outcome reporting, which precludes direct comparison. Here, we report a head-to-head comparison in three distinct experimental models to establish whether Wnt inhibition during neural stem cell, NSC (stage 1), or neural progenitor cell, NPC (stage 2), formation facilitates MGE differentiation. Wnt inhibition at both stages promotes MGE progenitor differentiation when compared to no inhibition. However, NSC (stage 1) Wnt inhibition markedly reduces the number of MGE progenitors available for downstream applications in the RD and the NAdD protocols due to early inhibition of proliferation. NPC (stage 2) Wnt inhibition in the adherent system is comparable to the EB-based methods offering a techically less challenging alternative.